Identification of Crowing Sound Characteristics of Pelung Chickens at the UNIGA Rector Cup Contest through Bioacoustic and Morphometric Approaches - Mulyana; Royani, Mega; Kusmayadi, Tendy (JURNAL ILMIAH PETERNAKAN TERPADU, 2025)
The Pelung chicken is known for its distinctive crow, which is the main criterion for judging in contests. However, the correlation between bioacoustics and morphometrics has rarely been studied. This study aims to describe the characteristics of Pelung chicken (Gallus gallus domesticus) crowing and its correlation with morphometrics. A survey method with a purposive sampling technique was used on 20 chickens in the general category and 20 chickens in the Jajangkar category at the 7th Rector Cup contest at Garut University on November 10, 2024. The observed variables were bioacoustics, including the number of syllables, vocalization duration, volume, and frequency, as well as morphometrics, including neck length, neck circumference, and body weight. The data were analyzed using the Mann-Whitney U test and the Spearman correlation test. Results showed that chickens in both categories had three syllables with a crowing duration of 10.10 seconds, a volume of 39.28 dB, and a frequency of 456.95 Hz in the general category. The Jajangkar category had a crowing duration of 9.15 seconds, a volume of 39.90 dB, and a frequency of 459.35 Hz. The Mann-Whitney U test revealed significant differences: the general category had a higher total duration and second syllable than the Jajangkar category. A significant positive correlation was found between body weight, voice volume, and voice frequency in the general category. In the Jajangkar category, neck length showed a significant positive correlation with duration and frequency. However, there was a significant negative correlation between body weight and frequency and between neck circumference and volume.